The Matarese countdown - Ludlum, Robert, 1927-2001. (New York : Bantam Books, 1997)
CIA case officer Cameron Pryce follows a trail of blood money and assassins in a rush to short circuit a plan by a group of international powerbrokers to seize control of the world's economy.
Adult.
Adult
Keywords: United States. -- Central Intelligence Agency -- Fiction; United States. -- Central Intelligence Agency -- Fiction; Assassins -- Fiction; Assassins -- Fiction; Spy stories